Job market requirements and qualities extraction for qualification analysis - Tigran R. Topchyan (АН Арм. ССР)
Analysis of the job market quali¯cation requirements is crucial for several various institutions responsible for the job market regulation as well as educational institutions. In this work we introduce the concept of quali¯cation requirements extraction from a large set of job descriptions presented in open format based on probabilistic topic models. This model is then used to gather valuable insight about the current trends in the IT, Financial and Engineering industries.
Keywords: Mathematics